Answer:(2+x/2)^6=64(1+3x/2+15x^2/16+5x^3/16+....) (2.05)^6=74.2203
Step-by-step explanation:
The last one
x^2-3X-28
Z Z Z Z Z
Answer:
The answer is below.
Step-by-step explanation:
The solution to the equation is p = 1/3 and q = undefined
<h3>How to solve the equation?</h3>
The equation is given as:
p^2 - 2qp + 1/q = (p - 1/3)
The best way to solve the above equation is by the use of a graphing calculator i.e. graphically
However, it can be solved algebraically too (to some extent)
Recall that the equation is given as:
p^2 - 2qp + 1/q = (p - 1/3)
Split the equation
So, we have
p^2 - 2qp + 1/q = 0
p - 1/3 = 0
Solve for p in p - 1/3 = 0
p = 1/3
Substitute p = 1/3 in p^2 - 2qp + 1/q = 0
So, we have
(1/3)^2 - 2q(1/3) + 1/q = 0
This gives
1/9 - 2/3q + 1/q = 0
This gives
2/3q + 1/q = -1/9
Multiply though by q
So, we have
2/3q^2 + 1 = -1/9q
Multiply through by 9
6q^2 + 9 = -q
So, we have
6q^2 + q + 9 = 0
Using the graphing calculator, we have
q = undefined
Hence. the solution to the equation is p = 1/3 and q = undefined
Read more about equations at:
brainly.com/question/13763238
#SPJ1